Differential expression of IL-6/IL-6R and MAO-A regulates invasion/angiogenesis in breast cancer. Issue 11 (29th May 2018) - Bharti, Rashmi; Dey, Goutam; Das, Anjan; Mandal, Mahitosh
Abstract Background Monoamine oxidases (MAO) are mitochondrial enzymes functioning in oxidative metabolism of monoamines. The action of MAO-A has been typically described in neuro-pharmacological domains. Here, we have established a co-relation between IL-6/IL-6R and MAO-A and their regulation in hypoxia induced invasion/angiogenesis. Methods We employed various in-vitro and in-vivo techniques and clinical samples. Results We studied a co-relation among MAO-A and IL-6/IL-6R and tumour angiogenesis/invasion in hypoxic environment in breast cancer model. Activation of IL-6/IL-6R and its downstream was found in hypoxic cancer cells. This elevation of IL-6/IL-6R caused sustained inhibition of MAO-A in hypoxic environment. Inhibition of IL-6R signalling or IL-6R siRNA increased MAO-A activity and inhibited tumour angiogenesis and invasion significantly in different models. Further, elevation of MAO-A with 5-azacytidine (5-Aza) modulated IL-6 mediated angiogenesis and invasive signatures including VEGF, MMPs and EMT in hypoxic breast cancer. High grade invasive ductal carcinoma (IDC) clinical specimen displayed elevated level of IL-6R and depleted MAO-A expression. Expression of VEGF and HIF-1α was unregulated and loss of E-Cadherin was observed in high grade IDC tissue specimen. Conclusions Suppression of MAO-A by IL-6/IL-6R activation promotes tumour angiogenesis and invasion in hypoxic breast cancer environment.